Determinants of Physical Activity Engagement and Physical Activity Intervention Adherence in Individuals with Mild Cognitive Impairment: A Mixed Methods Study - Connolly, Leona (Trinity College Dublin. School of Medicine. CentreFor Medical Gerontology, 2022)
The overarching aim of this thesis was to to identify the determinants of PA engagement and PA intervention adherence in individuals with MCI to expand on this under-researched topic and better inform PA promotion and intervention design in this cognitively at - risk population. This was a convergent parallel mixed methods study in a sample of participants of the NeuroExercise study, an RCT investigating the effects of a 12-month PA programme on cognitive function in individuals with MCI. Two main studies were conducted, study 1 investigated the determinants PA engagement and study 2 investigating the determinants of PA programme adherence. Each study comprised a qualitative and quantitative sub ? study, and an analysis of integrated findings. Quantitative data were statistically analysed to identify correlates. Qualitative data was collected and analysed inductively using thematic analysis to explore barriers and facilitators. Strands of findings were integrated using the COM ? B framework of behaviour. Levels of PA engagement and PA programme adherence are low. There was poor agreement between self-report and objectively measured PA engagement. Subjective accounts of memory impairment are associated with engagement and adherence, but not objective measures of cognitive function. Barriers were physical (physical capability/injury), cognitive (memory issues), practical (weather, lack of time) issues, low motivation for PA, and a lack of knowledge of the cognitive benefits of PA and PA guidelines. Class sessions resulted in better adherence than home based sessions, likely due to the practical and group support they provided. Individuals with MCI experience cognitive and physical limitations to PA that can be targeted to improve engagement in PA and adherence to PA programmes in this clinical group. This can be achieved through individualised PA assessment and prescription using self ? report cognitive and physical health data in conjunction with objective measurement to achieve a holistic perspective of capability for PA.
APPROVED
Keywords: Health research; Mild Cognitive Impairment; Physical Activity; Physical Activity Adherence